Trematodoses of the liver, bile ducts and pancreatic ducts (invasions caused by hepatic flukes) - S. B. Chuelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2020)
The paper summarizes the information currently available in the literature on the etiology, life cycles, epidemiology, pathogenesis, pathomorphology, clinical manifestations, diagnosis, etiotropic therapy, and prevention of human liver, bile ducts and pancreatic ducts trematodiases: fascioliasis, opisthorchiasis, clonorchiais, metorchiasis, pseudamphistomiasis, amphimeriasis, dicrocoeliasis, eurytremiasis.